An overview of health technology assessments of gene therapies with the focus on cost-effectiveness models - Michał Pochopień; Ewelina Paterak; Emilie Clay; Justyna Janik; Samuel Aballea; Małgorzata Biernikiewicz; Mondher Toumi (Journal of Market Access & Health Policy, 2021)
Background: Gene therapies can treat, prevent, or cure a disease by changing the expression of a person’s genes. They are an innovative strategy for treating genetic disorders; however, they are still emerging on the market access and in the healthcare system. Health technology assessment (HTA) agencies have not yet elaborated any standardised approach for assessing gene therapies; therefore, significant differences can be seen during HTAs carried out in various countries. In this review, we focused on submitted economic models of gene therapies approved for use by the US FDA and EMA with the aim to provide a comprehensive summary of how selected HTA bodies assessed the cost-effectiveness of gene therapies. An additional objective was to examine and discuss differences in the methods used in economic models across countries and drugs. Methods: We identified economic models of gene therapies from six countries (NICE, IQWiG, SMC, HAS, CADTH, ICER) and focused on nine agents (Glybera, Imlygic, Strimvelis, Yescarta, Kymriah, Luxturna, Zynteglo, Zolgensma, Tecartus). Details of cost-utility evaluations and budget impact models were reviewed and extracted. Results: Overall, 983 publications were identified, and 17 studies were included for the analysis. Reviewed evaluations of gene therapies differed in terms of the study perspective, discounting, extrapolation of outcomes based on limited and immature data, time horizon, and adequate estimation of benefits in terms of quality-adjusted life-years. Methods of economic evaluations were in line with the current recommendations; however, long-term follow-up studies are still missing. Conclusions: Discrepancies in an economic evaluation of gene therapies between different HTA bodies are rooted in a lack of general assessment frameworks specific to gene therapies. Although challenges were resolved by adjustments to the currently used value assessment framework, new methodological approaches would be useful. In addition, to improve the methods and quality of an evaluation, further research would be valuable.